Disclosure of government financial information and the cost of local government's debt financing: Empirical evidence from provincial investment bonds for urban construction - Zhibin Chen; Jun Pan; Liangliang Wang; Xiaofeng Shen (China Journal of Accounting Research, 2016)
China's slowing economic growth and rapid urbanization have made local government debt financing a significant issue. This study uses a sample of China's provincial government data for the 2006-2012 period to examine the effect of the disclosure of financial information by local governments on their debt financing costs. The results show that financial information disclosure is conducive to public supervision and enhances government credibility, leading to a decrease in the cost of debt financing. Furthermore, increased government economic intervention increases the strength of the association between financial information disclosure and the cost of debt financing. Increased government audit prevention function weakens the strength of the association between financial information disclosure and the cost of debt financing.
Keywords: 650; Local government debt; Cost of debt financing; Government financial information disclosure; Government intervention; Government audit